External Economic Partnership as a New Form to Create a Mechanism of Interaction Between Government and Business - M. A. Yakhjyaeva; A. Ya. Mortaza (Модернизация, инновация, развитие, 2017)
Purpose: the aim of the paper is to analyze the existing new forms of interaction between government and business in the context of foreign economic partnership and to support qualitatively new methodological tools in the field of study for its adaptation in domestic practice. Subject. The presented research topic is particularly relevant in the view of the fact that the external economic partnership is a new form of government and business interaction for the participation on the international market. In the first case, such activity is the development and implementation of tools supporting national export in business with an aim of creating a unified trade and financial policies, in the second – joint decisions within the framework of implementation of international projects of small and medium-sized enterprises (SME), increasing the role of sources of financing for SME. Methods: the methodological bases of this article are the economic and statistical methods of analysis, regulatory documents in the field of foreign economic partnership between state and business, public analytical materials in the subject area. Results: to study the tools of improvement of the strategic process, interaction between government and business, the author has studied foreign programs in this area and has identified relevant propositions for the practical implementation of the partnership within the FEP. Conclusions and Relevance: in addition to the features that determine the effectiveness of partnership between the state and business in the framework of FEP, there are the typical barriers. Keeping that in mind, the author substantiated recommendations towards breaching the barriers based on the application of legislative and regulatory settlement of questions regarding the interaction of partnership between the state and business in the framework of the FEP.